Wear and degradation of uhmwpe total hip replacement components - Kipping, Michael (2009)
Long term (>2 years) failure of UHMWPE components in-vivo is predominantly caused by wear of the UHMWPE component. The surface properties of UHMWPE greatly influence the adhesive and abrasive mechanisms of wear that occur in the hip. However, there is not a clear understanding of how in-vivo wear mechanisms influence surface mechanical properties of UHMWPE. In addition, previous researchers have reported wear rates for Charnley UHMWPE acetabular components that vary considerably between patients. It is conceivable that these variations in wear are a result of variations in the surface mechanical properties of UHMWPE.